Innovative Strategies to Prevent Childhood Smoking Epidemic: Systematic Review - Ahsanu Bil Husna; Ira Nurmala; Nendy Putra Salsabila (Universitas Airlangga, 2024)
Background: The phenomenon of smoking in children is a serious problem. There are still many minors who smoke and traders who still sell cigarettes to them. Although regulation regarding this issue has been established, legal attention to this problem is still fairly minimal; this shows the need for law enforcement and further protection for children. The rate of e-cigarette use among children aged 13–15 years is higher than adults across WHO regions. Aims: This research aimed to determine how efforts have been made to reduce smoking prevalence in children. Method: This literature study used a Systematic Literature Review (SLR). PubMed, Science Direct, ResearchGate, and Google Scholar were used for the literature search. The keywords used were